GWAS in Mice Maps Susceptibility to HIV-Associated Nephropathy to the Ssbp2 Locus. Issue 1 (January 2022) - Steers, Nicholas J.; Gupta, Yask; D'Agati, Vivette D.; Lim, Tze Y.; DeMaria, Natalia; Mo, Anna; Liang, Judy; Stevens, Kelsey O.; Ahram, Dina F.; Lam, Wan Yee; Gagea, Mihai; Nagarajan, Lalitha; et al.
Significance Statement: HIV-associated nephropathy (HIVAN) is a well-recognized complication of HIV infection that manifests with collapsing FSGS, tubular microcysts, interstitial fibrosis, and inflammation. Genetic predisposition to human HIVAN has been associated with variants of APOL1 ; however, the APOL1 risk alleles are incompletely penetrant, and it is very likely there are other common and rare risk genetic factors. Studying a validated mouse model of HIVAN, we found large differences in nephropathy susceptibility and severity among inbred strains. A genome-wide association study identified a major locus on Chr. 13 and suggests Ssbp2 as the candidate gene conferring susceptibility to HIVAN in the mouse. Identification of novel genes associated with HIVAN and other virally mediated glomerulopathies should foster the design of innovative therapeutics and better patient management. Visual Abstract: Abstract : Background: To gain insight into the pathogenesis of collapsing glomerulopathy, a rare form of FSGS that often arises in the setting of viral infections, we performed a genome-wide association study (GWAS) among inbred mouse strains using a murine model of HIV-1 associated nephropathy (HIVAN). Methods: We first generated F1 hybrids between HIV-1 transgenic mice on the FVB/NJ background and 20 inbred laboratory strains. Analysis of histology, BUN, and urinary NGAL demonstrated marked phenotypic variation among the transgenic F1 hybrids, providing strong evidence for host genetic factors in the predisposition to nephropathy. A GWAS in 365 transgenic F1 hybrids generated from these 20 inbred strains was performed. Results: We identified a genome-wide significant locus on chromosome 13-C3 and multiple additional suggestive loci. Crossannotation of the Chr. 13 locus, including single-cell transcriptomic analysis of wildtype and HIV-1 transgenic mouse kidneys, nominated Ssbp2 as the most likely candidate gene. Ssbp2 is highly expressed in podocytes, encodes a transcriptional cofactor that interacts with LDB1 and LMX1B, which are both previously implicated in FSGS. Consistent with these data, older Ssbp2 null mice spontaneously develop glomerulosclerosis, tubular casts, interstitial fibrosis, and inflammation, similar to the HIVAN mouse model. Conclusions: These findings demonstrate the utility of GWAS in mice to uncover host genetic factors for rare kidney traits and suggest Ssbp2 as susceptibility gene for HIVAN, potentially acting via the LDB1-LMX1B transcriptional network.